GRAMMATICAL AND LEXICAL COHESION IN “INDIA’S SUPREME COURT DECLARES HOMOSEXUAL SEX ILLEGAL” ARTICLE FROM EDITION.CNN.COM - FAUZIAH, VIERNA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: cohesion, grammatical cohesion, India’s Supreme Court DeclaresHomosexual Sex Illegal” article. Cohesion is the interconnection among sentences because of the formal factors or the internal factors in the language. The general function of cohesion is to make the discourse cohesive. One of the examples of discourse is an article. The article that is used in this study entitled “India’s Supreme Court Declares Homosexual Sex Illegal” by Harmeet Shah Singh and focus on homosexual sex. As we know, homosexual sex is a taboo and illegal, so that it is interesting to be discussed. The objectives of the study are to find out the grammatical and lexical cohesion devices in the article and to analyze the use of them in the article.The study uses qualitative approach. The data of the study are sentences of phrases which consist of grammatical and lexical cohesion in the article. The data source of this study is the article taken from cnn.com website in the edition column which was published on December 11th , 2013.The results of the study show that all kinds of grammatical cohesion can be found in the article, except substitution and verbal ellipsis. Reference is grammatical cohesion mostly use in the article, then followed by conjunction and ellipsis. In addition, all kinds of lexical cohesion can be found in the article, except synonym. The types of lexical cohesion are reiteration and collocation. Reiteration includes repetition, superordinate, and general words. Cohesion gives influences to the article and the article has fulfilled all those criteria from JS Badudu about language in journalism, namely brief, concise, simple, straight to the point, interesting, and clear.It can be concluded that the article is a cohesive one because it has texture in it because the writer uses the cohesion devices very well. It also consists of 5W+1H (what, where, who, when, and how). It is suggested that other researchers conduct further study about coherence because it is often related to cohesion.